A compact circularly polarized half‐mode substrate integrated waveguide‐based leaky‐wave antenna array with wide range of dual‐beam scanning. Issue 4 (10th January 2022) - Geng, Yunjie; Wang, Junhong; Li, Zheng; Li, Yujian; Chen, Meie; Zhang, Zhan
Abstract: In this article, a compact circularly polarized (CP) leaky‐wave antenna (LWA) array based on half‐mode substrate integrated waveguide (HMSIW) structure is proposed, which has the capability of dual‐beam scanning in wide range through broadside. This array consists of two HMSIW LWAs with periodic π‐shaped slots, which can excite‐first space harmonic mode with CP waves, and an HMSIW power‐recycling semicircular structure, which is designed between the end of the first LWA and the start of second LWA to generate two symmetrical scanning beams. Moreover, the structure of this array is optimized to make the two beams have similar gain values. The results validate that the proposed array has one CP beam scanning from −62 to 14° and another CP beam scanning from 60 to −16° when the operating frequency changes from 5.2 to 7.5 GHz. The measured gains and axial ratios are also given and show good agreements with the full‐wave simulated results.